Monoclonal anti-β1-adrenergic receptor antibodies activate G protein signaling in the absence of β-arrestin recruitment - Hutchings, Catherine J.; Cseke, Gabriella; Osborne, Greg; Woolard, Jeanette; Zhukov, Andrei; Koglin, Markus; Jazayeri, Ali; Pandya-Pathak, Jahnavi; Langmead, Christopher J.; Hill, Stephen J.; Weir, Malcolm; Marshall, Fiona H. (Taylor & Francis, 2013)
Thermostabilized G protein-coupled receptors used as antigens for in vivo immunization have resulted in the generation of functional agonistic anti-β1-adrenergic (β1AR) receptor monoclonal antibodies (mAbs). The focus of this study was to examine the pharmacology of these antibodies to evaluate their mechanistic activity at β1AR. Immunization with the β1AR stabilized receptor yielded five stable hybridoma clones, four of which expressed functional IgG, as determined in cell-based assays used to evaluate cAMP stimulation. The antibodies bind diverse epitopes associated with low nanomolar agonist activity at β1AR, and they appeared to show some degree of biased signaling as they were inactive in an assay measuring signaling through β-arrestin. In vitro characterization also verified different antibody-receptor interactions reflecting the different epitopes on the extracellular surface of β1AR to which the mAbs bind. The anti-β1AR mAbs only demonstrated agonist activity when in dimeric antibody format, but not as the monomeric Fab format, suggesting that agonist activation may be mediated through promoting receptor dimerization. Finally, we have also shown that at least one of these antibodies exhibits in vivo functional activity at a therapeutically-relevant dose producing an increase in heart rate consistent with β1AR agonism.